Challenges facing SMEs in the Western Cape townships with a focus on gender issues - Nyathi, Lomakhosi (Graduate School of Business (GSB), 2022)
The state of Small and Medium Enterprises (SMEs) is a key determinant of economic development globally. These enterprises account for almost 90% of firms in both developed and emerging markets. They are the engines of the economy that drives employment creation, poverty alleviation, tax provision, export income and better the lives of citizens. Despite the hype and investment in SME development, the world's vulnerable locations have not benefited from such development, amongst them are South African township SMEs who continue to face a multitude of challenges that hinder them from developing into sustainable business enterprises with a meaningful contribution to the economy. Amongst them, women owned SMEs face supplementary challenges, which are mostly gender based in nature. The study explored the challenges facing township SMEs in the Western Cape province and how the gender dynamics have played out in the face of SME stagnation. After identifying the challenges and gender dynamics, policy gaps were explored, and bridging strategies implored. To this end, the study employed a qualitative research approach covering a sample of 14 participants from three townships of Khayelitsha, Nyanga and Langa using a semi-structured questionnaire for in-depth interviews. The primary interviews were analysed using the six-step thematic approach. The study found lack of funding to be the most prominent challenge, resulting in inadequate operational resources such as equipment, SME owner upskilling and product marketing. The study also found crime and corruption, limited opportunities and market access, human resources as well as lack of financial and business administration skills to be the cause of stagnation of township SMEs. Apart from the umbrella challenges facing SMEs, the study found women SME owners to be facing additional challenges of gender-based discrimination, family responsibility, sexual harassment and crime. Government initiatives were found to be ineffective in addressing township SME challenges, SME owners have limited knowledge about the workings of these initiatives. They were found to be lacking fairness and transparency due to corruption.